Electrolytes Profile of Estrual Mucus of Gir Cows with Reference to Body Condition Score and Fertility - Gohel, Mukesh M; Kavani, Fulabhai S; Dhami, Arjun J; Hadiya, Kamlesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Fifty Gir cows of different reproductive status (10 = normal cyclic, 20 = repeat breeders and 20=induced estrus) were selected to determine the association of electrolytes mainly the macro-minerals profile of their estrual cervico-vaginal mucus (CVM) to their body condition score (BCS) and fertility post-AI. The overall pooled mean concentrations of calcium, inorganic phosphorus, magnesium, sodium and potassium obtained in CVM of Gir cows were 14.27 ± 0.33 mg/dL, 1.87 ± 0.13 mg/dL, 4.24 ± 0.10 mEq/L, 159.85 ± 5.52 mEq/L and 29.50 ± 0.78 mEq/L, respectively. The repeat breeding cows had significantly (p<0.01) higher calcium and lower inorganic phosphorus, sodium and potassium in their CVM than the normal cyclic and/or induced estrus cows. Similarly, the conceived cows, overall and of repeater group, had significantly (p < 0.05) lower calcium and higher phosphorus, sodium and potassium than the non-conceived cows. However, no such variation was found in the magnesium content of CVM of these groups. Further, the levels of calcium in CVM showed an increasing trend, while other elements showed a decreasing trend with an increase in BCS from 2.5 to 3.5 (on 0-5 point scale) in all three categories of animals, but the differences were not significant for BCS within the group/category. It was thus inferred that significantly increased or widened Ca:P ratio and absolute lower levels of sodium and potassium in CVM could be responsible for conception failure and repeat breeding in dairy cows.